PENEGAKAN HUKUM DI BIDANG PANGAN TERKAIT MIE FORMALIN DI WILAYAH POLDA JAWA TENGAH - I Nyoman Garjita; Gunarto Gunarto (UNISSULA Semarang, 2019)
This Research results that : a) The implementation of law enforcement in the field of food related to formalin noodles conducted by Central Java Police, based on the Law of the Republic of Indonesia Number 18 Year 2012 on Food, set forth in Article 132, Chapter XIV, on Investigation is described as follows: (1) In addition to the police officers of the Republic of Indonesia, certain civil servant officials whose scope of duties and responsibilities in the field of Food are given special powers as investigators to conduct investigations in criminal offenses in the field of Food in accordance with the provisions of laws and regulations in the field of Criminal Procedure Law. (2) The civil servant investigator (3) The civil servant investigator as referred to in paragraph (1) shall inform the commencement of investigation to the police investigator officer of the Republic of Indonesia. (4) If the exercise of authority referred to in paragraph (2) requires arrest and detention measures, civil servant investigators shall coordinate with the police investigating officers of the Republic of Indonesia in accordance with the provisions of legislation. (5) The civil servant investigator as referred to in paragraph (1) shall submit the results of the investigation to the prosecutor through the police investigating officer of the Republic of Indonesia. (6) The appointment of civil servant investigation officers and procedures and investigation processes shall be carried out in accordance with the provisions of laws and regulations. b) Obstacles from Witnesses: People who know about criminal events often avoid being made witnesses. Witnesses often ignore / evade an investigator's call for questioning. Thus from some of these constraints, especially in the investigation process conducted by Police Investigator of Central Java, the Investigator can handle it as follows: c) Perform performance professionally. Obey the code of ethics Polri. Running the rules of applicable legislation. Keywords: Law enforcement, food, Formal Noodles